ECONOMIC DEVELOPMENT BASED ON GENDER EQUALITY IN THE INTERPRETATION OF SEYYED ALI KHAMENEI: TOWARD GOLDEN INDONESIA - Nurul Khair (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2023)
In the context of MDGs (Millennium Development Goals), the enhancement of economic growth to alleviate poverty must be capable of driving the advancement of gender equality. Achieving gender equality entails eliminating developmental disparities between men and women across all fields. High gender equality will foster productivity, economic growth, and overall development efficiency. Gender discrimination remains prevalent in various aspects of life in Indonesia, with a trend towards improvement. This article discusses how gender equality contributes to boosting economic growth in Indonesia, drawing on an analysis of Seyyed Ali Khamenei's ideas to grasp the essence of economic development within the framework of gender equality. The research's objective is to analyze the role of gender equality in Indonesia's economic growth. Gender equality is assessed through indicators such as life expectancy, labor force participation rates, and the average years of schooling for women compared to men. Using panel data, this study reveals that the ratios of female-to-male life expectancy, female-to-male labor force participation rates, and female-to-male average years of schooling significantly enhance economic growth in Indonesia. Gender equality emerges as a key solution to bolster economic growth. The current role of women must no longer be underestimated, particularly in their economic contributions, underscoring the importance of women's economic empowerment programs.